Optimizing the scale-up production of fermented astragalus and its benefits to the performance and egg quality of laying hens - Dong, Weiwei; Fan, Zhanlei; Li, Panxian; Liu, Jun; Sun, Guoping; Peng, Nan; Liang, Yunxiang; Zhao, Shumiao (Frontiers in Microbiology, 2023)
Astragalus is a homologous medicine and food for benefits to human being and poultry rearing. Fermented astragalus (FA) is a valuable product by fermentation, but its scale-up production requires optimization and expansion of solid-state fermentation (SSF). In this study, Lactobacillus pentosus Stm was screened as the most suitable LAB strain for fermenting astragalus due to its excellent capacity. After optimization and expansion of SSF, LAB count and lactic acid content reached 206 × 108 cfu/g and 15.0%, respectively. Meanwhile, the content of bioactive compounds in FA was significantly enhanced. Feeding experiments with laying hens indicated that supplementary with FA in diet significantly facilitated the performance and egg quality, as evidenced by reduced feed-to-egg ratio and egg cholesterol. This was due to the promotion of intestinal health by shifting intestinal microbiota. Therefore, this is a systematical endeavor of producing scale-up FA with promising potential as a feed additive in the poultry breeding industry.